Revision of the leafhopper genus Orosius Distant, 1918 (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) in the Arabian Peninsula with the description of a new species - El-Sonbati, Saad A.; Wilson, Michael R.; Dhafer, Hathal M. Al (Zootaxa, 2019)
The genus Orosius Distant, 1918 is revised from the Arabian Peninsula. Four species are considered, two of them as new records, O. aegypticus Ghauri, 1966 stat. rev.; O. cellulosus (Lindberg, 1927). O. albicinctus Distant, 1918 has been previously recorded by Dlabola (1980). A new species, O. viraktamathi El-Sonbati & Wilson sp. n. is also described. A key to species is provided.